2016
DOI: 10.1007/s11027-016-9707-y
|View full text |Cite
|
Sign up to set email alerts
|

From site-level to regional adaptation planning for tropical commodities: cocoa in West Africa

Abstract: The production of tropical agricultural commodities, such as cocoa (Theobroma cacao) and coffee (Coffea spp.), the countries and communities engaged in it, and the industries dependent on these commodities, are vulnerable to climate change. This is especially so where a large percentage of the global supply is grown in a single geographical region. Fortunately, there is often considerable spatial heterogeneity in the vulnerability to climate change within affected regions, implying that local production losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 46 publications
2
51
1
Order By: Relevance
“…The most important strategy for decreasing HANPP in cocoa dominated landscapes is to encourage the cultivation of shade trees. Research has also shown that cocoa yields can increase with increasing canopy cover provided by shade trees (Schroth et al, 2017;Asare et al, 2019), further strengthening the case that the key to climate smart strategies for cocoa is the presence of shade trees. Increasing shade tree cover not only reduces HANPP, but has other benefits including increased biodiversity and possibly more resilience of the cocoa crop to climate extremes and regional warming (Rice and Greenberg, 2000;Schroth et al, 2016).…”
Section: Npp and Hanpp Of Complex Mosaic Landscapementioning
confidence: 90%
“…The most important strategy for decreasing HANPP in cocoa dominated landscapes is to encourage the cultivation of shade trees. Research has also shown that cocoa yields can increase with increasing canopy cover provided by shade trees (Schroth et al, 2017;Asare et al, 2019), further strengthening the case that the key to climate smart strategies for cocoa is the presence of shade trees. Increasing shade tree cover not only reduces HANPP, but has other benefits including increased biodiversity and possibly more resilience of the cocoa crop to climate extremes and regional warming (Rice and Greenberg, 2000;Schroth et al, 2016).…”
Section: Npp and Hanpp Of Complex Mosaic Landscapementioning
confidence: 90%
“…Cote d’Ivoire, the world largest cocoa producer, has also experienced a similar shift with such extreme climate event being a contributing factor to geographic shifts in production areas [ 8 ]. Such spatial and temporal variations in climatic events allow for the identification of farmers responses to climate change [ 4 , 8 , 9 ]. An increase in dry season maximum temperatures together with seasonal droughts are the main projected impacts of climate change within the West African cocoa belt [ 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variability in current climatic conditions within the cocoa belt of Ghana and Cote d’Ivoire has resulted in different levels of climate suitability [ 10 ]. Different types of climate change adaptation including incremental, systemic and transformative adaptation would be required at different locations within the cocoa belt of West Africa depending on the projected climatic changes [ 9 ]. Good to very good cocoa climate suitability is projected to continue shifting cocoa production to the more wet forest regions by 2050 [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The crop stands as the key component in chocolate products consumed throughout the globe [35]. Thus, being in the tropics where cocoa is grown and harvested, West Africa accounts for more than 70% of world cocoa production [36,37]. As such, cocoa farming has, therefore, become a major economic activity in many parts of West Africa, employing millions of small-scale farmers [33].…”
Section: Methodsmentioning
confidence: 99%
“…In the process, much of the ecological treasures especially the Guinean Rainforest (GRF) of West Africa, branded in the past two decades ago as a mega worldwide biodiversity epicenter or hot bed, had dropped to 18% of the original size at the beginning of the 21st of century. Having mentioned it earlier, the zone is renowned for its high cocoa output with a quartet of nations in West Africa, Ivory Coast, Ghana, Nigeria, and Cameroun responsible for 70% of international cocoa production in the past two decades [45,36]. Based on the rising levels of demands in the export markets, present estimates indicate that West Africa's cocoa output surged by 50% all through 1987 and 2007 with much of the increment triggered by far deeper encroachments on forested habitats, amounting to huge disappearances in biodiversity and elevated carbon discharges.…”
Section: Large Scale Deforestation In the Regionmentioning
confidence: 99%